Design of an intelligent system to control educational laboratory equipment based on a hybrid mini-power plant - Orobchuk, Bogdan; Buniak, Oleh; Sysak, Ivan; Babiuk, Serhii (Eastern-European Journal of Enterprise Technologies, 2023)
The object of research is the processes of energy conversion based on the use of alternative energy sources with an intelligent control system of actuators. This technological advancement is part of the equipment at the laboratory of dispatch control over power supply of Ternopil Ivan Puluj National Technical University. The research and the designed system could increase the level of training of future specialists for production activities during the educational process. Another task addressed was to provide technological production with practically trained specialists who could successfully work under conditions of its high automation and informatization. As a result of the research, an operating model of a hybrid solar mini-power plant and a controller with a Wi-Fi module were constructed. On the basis of the designed controller, an intelligent control system of actuators was built, which is powered by this power plant. Owing to the flexible configuration system, the controller is easily adjusted for various production tasks while the controller software provides the possibility of updating and expanding its functionality in the future. The controller has a web interface that allows monitoring and debugging from browsers without using specialized applications. A feature of the designed intelligent control system is that it can operate continuously owing to power from a hybrid solar power plant. The power plant built operates both from solar energy and from a centralized network and rechargeable batteries under an automatic mode. The results of research and technological advancements could be useful in forming practical skills of would-be specialists in the design and implementation of energy-efficient technologies, as well as intelligent control systems in the electric power industry